Assessing Fear‐avoidance Beliefs in Patients with Cervical Radiculopathy. (12th December 2012) - Dedering, Åsa; Börjesson, Tina
Abstract Background and Purpose The study sought to evaluate validity and reliability of the Fear Avoidance Beliefs Questionnaire and the Tampa Scale for Kinesiophobia in patients with cervical radiculopathy. Methods A test–retest design was used to test stability over time in 46 patients with cervical radiculopathy. Differences between patients and healthy subjects were also evaluated comparing the patients with 41 physically active and healthy subjects. The patients answered the Fear Avoidance Beliefs Questionnaire and the Tampa Scale for Kinesiophobia twice. To test for differences between the patients and the healthy subjects, the latter answered the same questionnaires once. Questionnaires about activity, personal factors and health were also used. Results The test–retest reliability assessed with weighted kappa was 0.68 for the Fear Avoidance Beliefs Questionnaire and 0.45 for the Tampa Scale for Kinesiophobia. Only six of the 11 single items of the Fear Avoidance Beliefs Questionnaire and none of the single items of the Tampa Scale of Kinesiophobia showed kappa coefficients exceeding 0.60 (good reliability). Patients with cervical radiculopathy rated significantly worse on the Fear Avoidance Beliefs Questionnaire and the Tampa Scale for Kinesiophobia than the healthy subjects did. Conclusions The Fear Avoidance Beliefs Questionnaire may be recommended for test–retest evaluations because 'good' reliability was found. The Tampa Scale for Kinesiophobia had only 'moderate' test–retest reliability, and this should be considered when using this scale in test–retest evaluations. Both questionnaires can discriminate between patients with cervical radiculopathy and healthy subjects. Copyright © 2012 John Wiley & Sons, Ltd.